Molecular diagnosis of Fusarium rot and shaggy stipe diseases associated with the cultivation of Agaricus bisporus mushroom - Sharma, V P; Singh, S K; Kumar, Satish; Sharma, S R (Mushroom Research, 2015)
Please see the full text